Abdominal tuberculosis in children: A real‐world experience of 218 cases from an endemic region. Issue 2 (20th August 2019) - Lal, Sadhna B; Bolia, Rishi; Menon, Jagadeesh V; Venkatesh, Vybhav; Bhatia, Anmol; Vaiphei, Kim; Yadav, Rakesh; Sethi, Sunil
Abstract : Background and Aim: Abdominal tuberculosis (ATB) in children poses a diagnostic challenge because of its nonspecific clinical features, which often delay the diagnosis. Our aim was to present our real‐world experience and provide an insight into the presentation, pattern of distribution, and diagnosis of the disease. Methods: A retrospective review was conducted of case records of all children ≤12 years of age diagnosed with ATB from January 2007 to January 2018. Clinical details and investigations were recorded and analyzed. Results: A total of 218 children (110 boys), with a median age of 10 (0.25–12) years, were included. There was a median delay of 4 (0.5–36) months in establishing the diagnosis. Abdominal pain, fever, and loss of weight were the most common presenting features, with the triad of symptoms present in 54%. Multiple intra‐abdominal sites were involved in 118 (54%) patients, with a combination of the gastrointestinal tract (I) and abdominal lymph nodes (L) being the most common (53/118). Among children with single‐site involvement ( n = 100), the most commonly involved was L in 39 (39%), followed by I in 35(35%). Loss of weight was more common in children with involvement of multiple sites (85/118 vs 60/100, P = 0.03). Overall, a confirmed diagnosis was possible in 94 participants (43.1%). Suggestive imaging had the highest diagnostic yield of 85%. Nine (4.1%) patients needed surgical management. Conclusion: A triad of abdominal pain, fever, and weight loss is suggestive of ATB. Multiple intra‐abdominal sites are frequently involved. Microbiological confirmation is possible in only one‐third of the cases. Abstract : A triad of abdominal pain, fever, and weight loss is suggestive of abdominal tuberculosis in children. Multiple intra‐abdominal sites are frequently involved. Microbiological confirmation is possible in only a third of the cases.